Birth Order and Divergent Thinking: A Meta-Analysis. Issue 4 (2nd October 2021) - Abdulla Alabbasi, Ahmed M.; Tadik, Harun; Acar, Selcuk; Runco, Mark A.
ABSTRACT: This meta-analysis examined the association of birth order and divergent thinking (DT). The main purpose was to examine how ordinal position (only, first, middle, or last-born) is related to creativity. The results from 27 studies ( k = 222; N = 4, 690) were analyzed using a multilevel approach. Because some previous studies compared first- vs. later-born children whereas others compared different ordinal positions, three datasets were analyzed: (a) first-born vs. later-born children, (b) only children vs. children with siblings, and (c) middle-born vs. later-born children. Results showed that first-borns had higher DT scores than later-born children ( g = −0.165, 95% CI [−0.012, −0.318], p = .046). Moderator analysis showed a significant interaction between gender and task modality with later-born males scoring lower on figural (but not verbal) DT than first-born males. No significant difference was found between only children and first-born children with siblings. In addition, the results showed a non-significant difference between middle- and later-born children; however, moderator analysis indicated that gender and age significantly explained some of the variability in the mean effect. Limitations and practical implications of the findings are discussed.